The COVID-19 Curtain: Can Past Communist Regimes Explain the Vaccination Divide in Europe? - Maria Ines Berniell; Yarine Fawaz; Anne Laferrere; Pedro Mira; Elizaveta Pronkina (Institute of Labor Economics (IZA), 2021)
As of November 2021, all former Communist countries from Central and Eastern Europe exhibit lower vaccination rates than Western European countries. Can institutional inheritance explain, at least in part, this heterogeneity in vaccination decisions across Europe? To study this question we exploit novel data from the second wave of the SHARE (Survey of Health, Ageing, and Retirement in Europe) Covid-19 Survey fielded in Summer 2021 that covers 27 European countries and Israel. First, we document lower Covid-19 vaccine take-up amongst individuals above 55 years old who were born under Communism in Europe. Next, we turn to reunified Germany to get closer to a causal effect of exposure to Iron curtain regimes. We find that exposure to the Communist regime in East Germany decreases one's probability to get vaccinated against Covid-19 by 8 percentage points, increases that of not wanting the vaccine by 4 percentage points. Both effects are quite large and statistically significant, and they hold when controlling for individual socio-economic and demographic characteristics. We identify low social capital -measured as voluntary work, political engagement, trust in people- as a plausible channel through which past Communist regimes would still affect individuals' preferences for Covid-19 vaccination.
Keywords: I15; I12; P36; Z18; 330; SHARELIFE; vaccination; Communism; COVID-19